Early Pregnancy Agricultural Pesticide Exposures and Risk of Gastroschisis among Offspring in the San Joaquin Valley of California - Shaw, Gary M. (Birth Defects Res A Clin Mol Teratol, 2014)
BACKGROUND: Prevalence of gastroschisis has inexplicably been increasing over the past few decades. Our intent was to explore whether early gestational exposures to pesticides were associated with risk of gastroschisis. METHODS: We used population-based data, accompanied by detailed information from maternal interviews as well as information on residential proximity to a large number of commercial pesticide applications during early pregnancy. The study population derived from the San Joaquin Valley of California (1997–2006). Cases were 156 infants/fetuses with gastroschisis and controls were 785 infants without birth defects. RESULTS: Among 22 chemical pesticide groups analyzed, none had an elevated odds ratio with an associated confidence interval that excluded 1.0, although exposure to the triazine group showed borderline significance. Among 36 specific pesticide chemicals analyzed, only exposure to petroleum distillates was associated with an elevated risk, odds ratio = 2.5 (1.1–5.6). In general, a substantially different inference was not derived when analyses were stratified by maternal age or when risk estimation included adjustment for race/ethnicity, body mass index, folic acid supplement use, and smoking. CONCLUSION: Our study rigorously adds to the scant literature on this topic. Our a priori expectation was that we would observe certain pesticide compounds to be particularly associated with young age owing to the disproportionate risk observed for young women to have offspring with gastroschisis. We did not observe an exposure profile unique to young women.